Effect of Freezing on Seminal Characteristics of Jersey, Sahiwal and their Halfbred Bulls - SINGH, S P; PANDIT, R K; BHADORIA, H B S (The Indian Journal of Animal Reproduction, 2023)
Various seminal attributes have been creditep with fertility which appear to be affected by freezing process. Therefore, it is needed to observe the relative effect of processing frozen semen on these attributes. Hazards of semen freezing are not sustained alike by sperms of all the bulls as viability and morphology of the spermatozoa depends upon individual bull’s resistance . .. The eff ct of freezing on spermatozoa! motility, live per cent, abnormalities, biometry and glutamic oxalacetic transaminase (GOT) release was studied in Jersey (J), Sahiwal (S) and ½J ½S bulls semen.